2011
DOI: 10.5761/atcs.oa.09.01520
|View full text |Cite
|
Sign up to set email alerts
|

Lung Metastasectomy for Colorectal Carcinoma in Patients with a History of Hepatic Metastasis

Abstract: Background: We reviewed resection of pulmonary metastases preformed by the Department of Thoracic Surgery at Kyoto University Hospital to confirm the clinical significance of this surgery in patients with colorectal carcinoma and a history of hepatic metastasis. Methods: From 1992 to 2006, 19 patients with colorectal carcinoma and a history of hepatic metastasis underwent a pulmonary metastasectomy . Surgical outcomes of these patients were investigated in terms of various perioperative variables. Results: Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…arguing that resection is not warranted in patients with simultaneous hepatic and pulmonary metastases (5‐year survival rate 0 per cent versus 44 per cent in patients with sequentially detected pulmonary metastases). Similarly, Chen and colleagues reported that no patients with simultaneous hepatopulmonary CRC metastases were alive at 3 years, and Kawano et al . found a relative risk of 3·73 on multivariable regression analysis for patients presenting with simultaneous hepatopulmonary disease.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…arguing that resection is not warranted in patients with simultaneous hepatic and pulmonary metastases (5‐year survival rate 0 per cent versus 44 per cent in patients with sequentially detected pulmonary metastases). Similarly, Chen and colleagues reported that no patients with simultaneous hepatopulmonary CRC metastases were alive at 3 years, and Kawano et al . found a relative risk of 3·73 on multivariable regression analysis for patients presenting with simultaneous hepatopulmonary disease.…”
Section: Discussionmentioning
confidence: 92%
“…For all studies, the overall survival (OS), and 1-and 5-year survival rates are for the total patient cohort. Survival is presented variably in the literature: from the last pulmonary metastectomy 4,7,10,14,16 ; from the first pulmonary metastectomy 13,15,19,20 ; from the diagnosis of metastatic disease 3 ; from diagnosis of the primary tumour 12,13,18 ; and sometimes not clear if mixed 8,11,17 . *Simultaneous disease defined as metastases presenting less than 3 months apart.…”
Section: Introductionmentioning
confidence: 99%
“…We selected 29 papers that met all the selection criteria and divided them into two broad groups: 6 which did not analyse the variable of interest [2], [6], [7], [11], [12], [13], that is, whether patients who underwent surgery had a history of resected liver metastases; and the other 23 which did consider this variable [1], [5], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33]. In this second group of 23 papers, there were 21 patient series, 1 prospective [15] and the others retrospective [5], [14], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30],…”
Section: Studies Includedmentioning
confidence: 99%
“…In total, we collected data from 17 studies [2], [5], [12], [13], [14], [16], [17], [18], [20], [21], [25], [26], [27], [28], [30], [32], [33], managing to obtain data on 3501 patients for the meta-analysis of individual data. The authors from three studies [6], [15], [31] replied to the first email, expressing interest in the study, but did not communicate further, and did not provide any information or explain their reasons; one author replied declining to participate in the study [19]; and authors of the other studies [7], [11], [22], [23], [24], [29] did not respond to any of our attempts to contact them.…”
Section: Studies Includedmentioning
confidence: 99%
“…3,5e15 Simultaneous colorectal liver and lung metastases (SLLM) is the most frequent combination of multiple metastases of colorectal cancer. 5e7,10,12e14, 16,17 Lung metastases constitute one-third of cases of concomitant metastases with CLM, 11 and the prognosis of SLLM treated with chemotherapy is dismal [estimated 3-year overall survival (OS) rate of <15%]. 18 One report suggested that simultaneous rather than sequential detection of liver and lung metastases of colorectal cancer does not warrant resection because of the poor postsurgical outcomes 19 ; however, further subclassification of patients with SLLM might allow for identification of patients who have a more favorable prognosis.…”
Section: Introductionmentioning
confidence: 99%